A high-strength, corrosion-resistant ultrafine-grained WC-Ni-based cemented carbide and its preparation method

By adding components such as Cr3C2, VC, Mo2C and AlN to WC-Ni-based cemented carbide, and using three-dimensional motion dry premix, wet grinding and liquid phase sintering, high-strength, corrosion-resistant ultrafine crystal WC-Ni-based cemented carbide, solving the problem of insufficient performance in the application of core main pumps, and achieving comprehensive performance improvements of high strength, corrosion resistance and wear resistance.

CN118497583BActive Publication Date: 2025-04-15ZHUZHOU HARD ALLOY GRP CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410546373.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-06
Publication Date
2025-04-15
Estimated Expiration
2044-05-06

AI Technical Summary

Technical Problem

In the application of key components of core main pump mechanical seals, existing WC-Ni-based cemented carbides are difficult to meet the strict requirements of strength, corrosion resistance, wear resistance and performance stability, and the use of Co will lead to nuclear contamination.

Method used

High-strength, corrosion-resistant ultrafine crystal WC-Ni-based cemented carbide with components such as WC, Ni, Cr3C2, VC, Mo2C and AlN are used to control the WC grain size to be less than 0.5μm to form Ni3Al nano-dispersed phase to enhance the strength and corrosion resistance of the alloy.

Benefits of technology

It significantly improves the flexural strength, Vickers hardness and wear resistance of the alloy, reduces the annual corrosion rate, and meets the strict requirements of the mechanical seal of the nuclear main pump for material components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118497583B_ABST
    Figure CN118497583B_ABST
Patent Text Reader

Abstract

The present invention discloses a high-strength, corrosion-resistant ultrafine-grained WC-Ni-based hard alloy and a preparation method thereof. The alloy is composed of WC, Ni, composite grain growth inhibitors Cr3C2, VC and Mo2C, and bonding phase strengthening additive AlN; the average grain size of the WC hard phase is less than or equal to 0.5 μm, and there is an in-situ formed Ni3Al nano-dispersed phase in the Ni-based bonding phase. The preparation method of the present invention adopts integrated mixed material preparation of three-dimensional motion dry premixing and high-efficiency wet grinding in mixed wet grinding media, instantaneous high-temperature activation and cooling two-stage liquid phase pressure sintering, local temperature section rapid cooling after cooling liquid phase pressure sintering insulation, low-temperature tempering and other processes to achieve ultrafine grain strengthening and solid solution strengthening of the bonding phase, nano-dispersed phase strengthening and corrosion resistance strengthening, significantly reduce interphase galvanic corrosion of the alloy, and improve the comprehensive performance of the alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a high-strength, corrosion-resistant ultrafine-grained WC-Ni-based hard alloy and a preparation method thereof, and belongs to the field of high-performance ultrafine-grained hard alloy new materials for wear-resistant parts suitable for the field of low-carbon clean energy. Background Art

[0002] Nuclear energy is an important component of low-carbon clean energy. The nuclear main pump is a key component that drives the coolant to circulate in the reactor coolant system and maintains the safe operation of the nuclear reactor. Its key mechanical seal components are in extreme service conditions such as radiation, corrosive media, friction and wear for a long time, so the material has extremely high requirements for radiation resistance, corrosion resistance and wear resistance, and cemented carbide is usually used. Co is the most commonly used bonding metal for cemented carbide, with excellent physical and mechanical properties, but Co can form radioactive isotopes in a service environment that can cause nuclear transmutation, which will cause the alloy performance to significantly deteriorate and form nuclear pollution; in addition, compared with Ni, Co's corrosion resistance is significantly lower. Therefore, WC-Ni-based cemented carbide has become the best choice for the material of key mechanical seal components of nuclear main pumps.

[0003] The hardness and strength of hard composite materials are greatly affected by the phase characteristics and volume fraction of the alloy. The Vickers hardness of Co and Ni is 1784MPa and 784MPa respectively. The stacking fault energy, which is negatively correlated with the work hardening ability and crack growth resistance, is 20mJ / m 2 and 125mJ / m 2 Therefore, compared with WC-Co cemented carbide, it is difficult to improve the hardness, strength and other properties of pure WC-Ni cemented carbide, which seriously limits the expansion of its application field; secondly, since the use of reduced or electrolytic Ni powder is difficult to meet the production needs of high-performance WC-Ni based alloys due to its coarse particle size and low purity, carbonyl Ni powder is currently commonly used as raw material, but the surface of carbonyl Ni powder is rough, which makes it difficult to disperse evenly during the preparation of wet grinding mixture, resulting in the aggregation of bonding phases in the alloy microstructure; in addition, fine grain strengthening is an important means to improve the strength, hardness and wear resistance of alloys. Compared with WC-Co alloys, the liquid phase of WC-Ni alloys has a temperature increase of 40 to 70 °C, and the Ni / Co vapor pressure ratio under liquid phase sintering conditions is close to 10. Therefore, during the sintering process of WC-Ni alloys, the WC grain growth driving force is large and Ni evaporates significantly, making it difficult to obtain alloys with fine WC grains and uniform microstructure. The bending strength of traditional pure WC-Ni cemented carbide is usually lower than 2300MPa. The Rockwell hardness HRA, which is positively correlated with wear resistance under the conditions of the same grain size and the same bonding metal content, is more than 0.5 lower than that of WC-Co alloy. Therefore, its comprehensive performance is difficult to meet the stringent requirements of mechanical seals on nuclear main pumps for the strength, corrosion resistance, wear resistance and performance stability of WC-Ni based cemented carbide material components.

[0004] Chinese patent CN101205584A "A high hardness, high strength, low-cost non-magnetic cemented carbide" discloses that the alloy composition is 80-90 parts of WC, 5-20 parts of Ni, 0.5-5 parts of chromium carbide, 0.1-0.5 parts of vanadium carbide, and 0.1-0.5 parts of molybdenum carbide. The WC grain size in the alloy is 1.8-2.4μm, which belongs to the medium-coarse alloy grain size range. The porosity of the alloy prepared by this patent is as high as A06 and B06. High porosity will cause abnormal failure of key components of the mechanical seal of the nuclear main pump, seriously affecting the safe operation of the equipment. Chinese patent CN107964620A "Reinforced cemented carbide based on tungsten nickel and its preparation method" discloses a cemented carbide with an alloy composition of WC-9%Ni-(0.1-0.3%)Cr3C2-(0.02-1%)AlN, and its content does not involve the alloy microstructure and physical and mechanical properties. Judging from the disclosed preparation method, the alloy is not an ultrafine-grained alloy. The patent does not involve the regulation of the existence state of AlN in the alloy. The addition of AlN only improves the alloy's resistance to high-temperature oxidation and thermal conductivity. Obviously, the alloy cannot be used as the material for key components of the nuclear main pump mechanical seal. Summary of the invention

[0005] One object of the present invention is to provide a high-strength, corrosion-resistant and high-performance ultrafine-grained WC-Ni based cemented carbide suitable for key parts of nuclear main pump mechanical seals.

[0006] In order to achieve the above-mentioned purpose, the high-strength, corrosion-resistant and high-performance ultrafine-grained WC-Ni based cemented carbide alloy of the present invention is composed of WC, bonding metal Ni, a composite grain growth inhibitor and a bonding phase strengthening additive, wherein the composite grain growth inhibitor is Cr3C2, VC and Mo2C, and the bonding phase strengthening additive is AlN; the mass fraction of the bonding metal Ni in the alloy is 6.0-11.0%; the mass ratio of the grain growth inhibitor Cr3C2 to Ni is 8.0-10.0%, the mass ratio of VC to Ni is 3.0-4.0%, and the mass ratio of Mo2C to Ni is 5.0-7.5%; the mass ratio of the bonding phase strengthening additive AlN to Ni is 4.0-6.0%; the average grain size of the WC hard phase in the WC-Ni based cemented carbide is less than or equal to 0.5μm, and there is an in-situ formed Ni3Al nano-dispersed phase in the Ni-based bonding phase.

[0007] Another object of the present invention is to provide a method for preparing high-strength, corrosion-resistant ultrafine-grained WC-Ni based cemented carbide.

[0008] In order to achieve the above object, the preparation method of the present invention comprises:

[0009] A. Batching and dry premixing: WC powder with a specific surface area average particle size of less than 0.25 μm, carbonyl Ni powder with a Fisher particle size of less than 1.5 μm, and Cr3C2 powder, VC powder, Mo2C powder and AlN powder with a Fisher particle size of less than 1.2 μm are batched so that the mass fraction of Ni in the raw material powder is 6.0-11.0%, the mass ratio of Cr3C2 to Ni is 8.0-10.0%, the mass ratio of VC to Ni is 3.0-4.0%, the mass ratio of Mo2C to Ni is 5.0-7.5%, and the mass ratio of AlN to Ni is 4.0-6.0%; then the prepared raw material powders are dry mixed for 1-1.5 hours under a protective atmosphere to prepare a premix;

[0010] B. Wet grinding: wet grinding the cemented carbide grinding balls, premix, molding agent and wet grinding medium for 50 to 60 hours, wherein the mass ratio of cemented carbide grinding balls to premix is ​​4 to 5, and the molding agent is added in an amount of 2.0 to 2.3% of the total mass fraction of the powder;

[0011] C. Drying and granulation: using spray drying granulation or vacuum drying and mechanical granulation process, the wet-milled mixture is prepared into a spherical mixture with an average particle size of less than 150 μm;

[0012] D. Molding: According to the shape and size of the product, the spherical mixture is pressed into shape;

[0013] E. Removal of forming agent and sintering: a. Remove the forming agent from the green compact; b. Raise the temperature at a heating rate of 3 to 5°C / min for vacuum sintering. When the sintering furnace temperature rises to 1300 to 1350°C, introduce high-purity argon gas to make the pressure in the furnace reach 6 to 8 kPa, and keep it warm for 50 to 70 minutes; c. Raise the temperature in the furnace to 1420 to 1440°C at a heating rate of 5 to 10°C / min, and then increase the amount of high-purity argon gas in the furnace to raise the pressure in the sintering furnace to 4 to 8MPa; d. Maintain the pressure in the furnace at 4-8MPa, continue to heat up to 1450-1470℃ at a rate of 10-20℃ / min, and keep warm for 10-15 minutes; e. Continue to maintain the pressure in the furnace at 4-8MPa, cool down to 1420-1440℃ at a rate of 10-20℃ / min, and keep warm for 60-100 minutes; f. Reduce the furnace temperature to 1100-1200℃ within 5-10 minutes; g. Cool with the furnace to the product discharge temperature;

[0014] F. Low temperature tempering: The tempering temperature is 350-450℃, the tempering time is 3-10 hours, and it is carried out under a protective atmosphere.

[0015] The dry mixing of raw material powders into a premix in step A is carried out in a three-dimensional motion dry mixing device.

[0016] The protective atmosphere in step A is high-purity argon or high-purity nitrogen.

[0017] The wet grinding in step B is carried out in a drum ball mill, and the molding agent is paraffin or polyethylene glycol.

[0018] The grinding ball material in step B is WC-Ni based cemented carbide with an average grain size of WC hard phase less than 0.8 μm.

[0019] The wet grinding medium in step B is a mixed solution of alcohol and hexane, the volume proportion of hexane in the wet grinding medium mixed solution is 5-10%, and the wet grinding medium liquid level is 5-7 cm higher than the ball and material solid phase reference level.

[0020] In step B, the molding agent is polyethylene glycol or paraffin.

[0021] The protective atmosphere in step F is vacuum or high-purity argon or high-purity nitrogen inert gas.

[0022] Before step F of low temperature tempering, the sintered product may be subjected to mechanical processing.

[0023] The present invention prevents Cr, V, Mo and Al from existing in the alloy as an independent third phase through component and preparation process design, computational simulation and experimental verification; gives full play to the synergistic effect of the composite grain growth inhibitor of the three components of Cr3C2, VC and Mo2C on the maximum reduction of the temperature of the liquid phase of the alloy system, significantly reduces the sintering temperature required for achieving full densification of the alloy, and effectively prevents the evaporation loss of Ni; effectively inhibits the continuous and discontinuous grain growth of WC grains through the reduction of sintering temperature, the synergistic and effective regulation of the dissolution and precipitation behavior of WC grains by the composite grain growth inhibitor and the regulation of relevant process parameters, so as to make WC The average grain size of the hard phase is less than 0.5μm; the strength and hardness of the alloy as well as the wear resistance of the alloy which is positively correlated with the hardness can be significantly improved through fine grain strengthening; through composition optimization and adaptability regulation of the preparation process, W, Cr, V, and Mo form solid solution strengthening on the Ni-based bonding phase, and Ni3Al nano-dispersed phase strengthening is formed in situ in the Ni-based bonding phase, which effectively reduces the galvanic corrosion between the WC hard phase and the bonding phase of the alloy system, and significantly improves the hardness, corrosion resistance and wear resistance of the bonding phase and the alloy. The alloy has a bending strength of up to 3950MPa and a Vickers hardness HV30 of up to 2030kgf / mm 2 The annual corrosion rate in 3.5% NaCl solution can be as low as 10.1μm / a, which can meet the stringent requirements of mechanical seals on nuclear main pumps for the strength, corrosion resistance, wear resistance and performance stability of WC-Ni based cemented carbide parts.

[0024] The present invention adds a three-dimensional motion dry premixing process of raw material powder before the traditional wet grinding process. The three-dimensional motion mixing will not cause shear force to be formed in the powder, which is conducive to efficient and uniform mixing of powders with different particle sizes, different morphologies and different theoretical densities, and is particularly suitable for uniform mixing of rough-surface carbonyl Ni powder and other powders.

[0025] The present invention adopts a two-component mixed wet grinding medium of alcohol and hexane. The combined system formed by the mixed wet grinding medium and the forming agent can form a surfactant stabilization and polymer stabilization effect, which can improve the wettability of the wet grinding medium to the powder, thereby promoting the penetration of the wet grinding medium at the defects of the powder particles and the crushing of the powder particles, achieving the deagglomeration and dispersion of high specific surface area powder agglomerates and rough surface powders, and improving the grinding and dispersion efficiency during the wet grinding process. The present invention can effectively improve the homogeneity and product quality stability of the wet grinding mixture through a two-step integrated mixed material preparation process of dry mixing and wet grinding.

[0026] The finer the metal powder, the larger its specific surface area, the more difficult it is to disperse, the easier it is to add oxygen, and the more complicated the carbon thermal reduction reaction process during sintering. Because the alloy additive can be dissolved in Ni during the liquid phase sintering process, the raw material adaptability is designed through the mixed material preparation process and the sintering process. The present invention uses commercial alloy additive powder and carbonyl Ni powder with a slightly coarser particle size than WC powder commonly seen in the market, which is conducive to the precise oxygen and carbon control of the alloy system, improves the product quality stability, and also reduces the production cost.

[0027] In terms of sintering process, based on the WC grain growth activation energy and WC grain growth phase field simulation obtained by the inventors, the wettability of Ni melt to WC grains and the uniformity of Ni melt distribution are improved by instantaneous high-temperature activated liquid phase pressure sintering under 4-8MPa high-purity argon loading conditions, accelerating the dissolution of alloy additives in Ni melt, and promoting the rapid homogenization of alloy components. After instantaneous high-temperature activated liquid phase pressure sintering, the temperature is lowered, and the cooling liquid phase pressure sintering is performed under 4-8MPa high-purity argon loading conditions. While the pressure-assisted liquid phase filling realizes the full densification of the alloy, the low-temperature liquid phase pressure sintering can effectively enhance the inhibitory effect of grain growth inhibitors on WC grain growth. After the cooling liquid phase pressure sintering insulation is completed, the rapid cooling process is used to cool down to the liquid phase solidification temperature, which can effectively inhibit the precipitation of solute atoms in Ni, achieve supersaturation of solid solution atoms in the Ni-based bonding phase, and is conducive to passivating the edges and corners of WC grains and preventing stress concentration in the alloy, thereby increasing the fracture toughness and compressive strength of the alloy; at the same time, it can effectively increase the solid solution strengthening effect in the bonding phase, improve the hardness of the alloy, and further improve the corrosion resistance and wear resistance of the alloy. The present invention is different from the traditional rapid cooling process that directly drops from the sintering temperature to the furnace temperature. It only uses a rapid cooling process to cool down to the liquid phase solidification temperature after the cooling liquid phase pressure sintering insulation is completed, which can effectively prevent the cooling deformation of large products and special-shaped products.

[0028] Based on the induction of the intrinsic characteristics of the phase, the new phase is formed in situ from the parent phase matrix, and can usually exist in the matrix in the form of a coherent or semi-coherent nano-dispersed phase. Rapid cooling in the sintering temperature range and low-temperature tempering after sintering can form a Ni3Al nano-dispersed phase in situ in the supersaturated Ni-based bonding phase, achieving the strengthening of the bonding phase by the nano-dispersed phase. At the same time, low-temperature tempering is also conducive to the release of surface processing stress of the alloy product after grinding. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a scanning electron microscope photograph of the microstructure of the WC–6.0Ni–0.48Cr3C2–0.18VC–0.30Mo2C–0.24AlN alloy in Example 1.

[0030] Figure 2 This is a scanning electron microscope photograph of the microstructure of the WC-6.0Ni-0.48Cr3C2-0.18VC-0.30Mo2C-0.24AlN alloy prepared in Example 1 without rapid cooling during sintering and without tempering process after sintering.

[0031] Figure 3 This is a scanning electron microscope photograph of the microstructure of the WC–6.0Ni–0.48Cr3C2–0.18VC–0.30Mo2C–0.24AlN alloy prepared by sintering at 1470°C for 120 minutes in Example 2.

[0032] Figure 4 This is a scanning electron microscope photograph of the microstructure of the WC–6.0Ni–0.48Cr3C2–0.18VC–0.30Mo2C–0.24AlN alloy prepared by directly wet grinding the raw materials in Example 3 in a single alcohol wet grinding medium. DETAILED DESCRIPTION

[0033] The present invention will be further described below in conjunction with the embodiments and drawings.

[0034] Example 1

[0035] A. Batching and dry premixing: WC powder with a specific surface area average particle size of 0.20 μm, carbonyl Ni powder with a Fisher particle size of 1.2 μm, and Cr3C2 powder with a Fisher particle size of 0.8 μm, VC powder with a Fisher particle size of 1.1 μm, Mo2C powder with a Fisher particle size of 1.0 μm, and AlN powder with a Fisher particle size of 0.9 μm, respectively, are batched so that the mass fraction of Ni in the raw material powder is 6.0%, the mass ratio of Cr3C2 to Ni is 8.0%, the mass ratio of VC to Ni is 3.0%, the mass ratio of Mo2C to Ni is 5.0%, and the mass ratio of AlN to Ni is 4.0%; the prepared raw material powders are then charged into a three-dimensional mixing device and dry mixed for 1.5 hours in a high-purity argon protective atmosphere to prepare a premix;

[0036] B. Wet grinding: using a drum-type ball mill and WC-8Ni-based cemented carbide grinding balls with an average grain size of 0.7 μm, the mass ratio of grinding balls to premix is ​​5:1, the grinding balls, the premix obtained in step A, a paraffin molding agent accounting for 2.3% of the total mass of the mixture, and a wet grinding medium mixed with alcohol and hexane are added into a ball mill barrel, and the wet grinding time is 50 hours; the volume proportion of hexane in the wet grinding medium mixed solution is 10%, and the wet grinding medium liquid level is 5 cm higher than the solid phase reference plane of the balls and the material;

[0037] C. Drying and granulation: using a spray drying granulation process, the wet-milled mixture is prepared into a spherical mixture with an average particle size of less than 150 μm;

[0038] D. Molding: According to the shape and size of the product, the spherical mixture is pressed into shape by the molding process;

[0039] E. Forming agent removal and sintering: Forming agent removal and sintering are carried out in a 10MPa pressure sintering furnace. Forming agent removal is carried out in a hydrogen atmosphere according to the conventional paraffin removal process. Vacuum sintering is carried out at a heating rate of 5°C / min. When the temperature in the furnace rises to 1350°C, high-purity argon is introduced to make the pressure in the sintering furnace reach 6kPa and keep warm for 50 minutes. When the temperature in the furnace is raised to 1440°C at a heating rate of 10°C / min, the amount of high-purity argon in the furnace is increased to make the furnace The pressure rises to 8MPa. When the pressure in the furnace reaches 8MPa, the temperature is raised to 1470℃ at a heating rate of 20℃ / min, and kept at this temperature for 15 minutes to perform instantaneous high-temperature activated liquid phase pressure sintering. Then, the pressure in the furnace is maintained at 8MPa, and the temperature in the furnace is lowered to 1440℃ at a cooling rate of 10℃ / min, and kept at this temperature for 100 minutes to perform cooling liquid phase pressure sintering. After the insulation is completed, the furnace temperature is lowered to 1200℃ within 10 minutes, and then cooled to the discharge temperature with the furnace.

[0040] F. Low temperature tempering: The ground and polished machined alloy is tempered at 450°C in a vacuum furnace for 3 hours.

[0041] The microstructural inspection was carried out in accordance with GB / T 3488.4-2022 "Metallographic determination of cemented carbide microstructure Part 4: Metallographic determination of porosity, uncombined carbon defects and decarburization phases". The results showed that the porosity of the alloy was <A02, B00, and it was in a fully densified state. There was no decarburization phase or carburized phase in the alloy. Figure 1As shown in the figure, the microstructure of the alloy after corrosion by standard metallographic reagents was observed under a scanning electron microscope. The results showed that the alloy had a two-phase homogeneous structure of WC hard phase and Ni-based solid solution bonding phase, with no obvious abnormal growth of WC grains, and the edges and corners of WC grains were blunted. According to GB / T 3488.2-2018 "Metallographic determination of cemented carbide microstructure Part 2: Measurement of WC grain size", the average intercept method was used to measure three electron microscope photos taken at a magnification of 20,000 times. The results showed that the average grain size of WC in the alloy was 0.28μm. The transmission electron microscopy observation and analysis results showed that there was a uniformly distributed Ni3Al nano-dispersed phase in the alloy bonding phase.

[0042] Example 2

[0043] A. Batching and dry premixing: WC powder with a specific surface area average particle size of 0.22 μm, carbonyl Ni powder with a Fisher particle size of 1.1 μm, and Cr3C2 powder with a Fisher particle size of 0.8 μm, VC powder with a Fisher particle size of 1.0 μm, Mo2C powder with a Fisher particle size of 1.1 μm, and AlN powder with a Fisher particle size of 0.8 μm, respectively, are batched so that the mass fraction of Ni in the raw material powder is 8.0%, the mass ratio of Cr3C2 to Ni is 10.0%, the mass ratio of VC to Ni is 3.0%, the mass ratio of Mo2C to Ni is 6.0%, and the mass ratio of AlN to Ni is 5.0%; then the prepared raw material powders are charged into a three-dimensional mixing device, and dry mixed for 1 hour under a high-purity nitrogen protective atmosphere to prepare a premix;

[0044] B. Wet grinding: using a drum-type ball mill and WC-8Ni-based cemented carbide grinding balls with an average grain size of 0.7 μm, the mass ratio of grinding balls to premix is ​​4:1, the grinding balls, the premix obtained in step A, a polyethylene glycol forming agent accounting for 2.3% of the total mass of the mixture, and a wet grinding medium mixed with alcohol and hexane are added into a ball mill barrel, and the wet grinding time is 60 hours; the volume proportion of hexane in the wet grinding medium mixed solution is 5%, and the wet grinding medium liquid level is 6 cm higher than the solid phase reference plane of the balls and the material;

[0045] C. Drying and granulation: using a spray drying granulation process, the wet-milled mixture is prepared into a spherical mixture with an average particle size of less than 150 μm;

[0046] D. Molding: According to the shape and size of the product, the spherical mixture is pressed into shape by the molding process;

[0047] E. Forming agent removal and sintering: Forming agent removal and sintering are carried out in a 10MPa pressure sintering furnace. Forming agent removal is carried out in a hydrogen atmosphere according to the conventional polyethylene glycol removal process. Vacuum sintering is carried out at a heating rate of 3°C / min. When the furnace temperature rises to 1320°C, high-purity argon is introduced to make the pressure in the sintering furnace reach 7kPa and keep warm for 60 minutes. When the furnace temperature rises to 1430°C at a heating rate of 10°C / min, the amount of high-purity argon loaded in the furnace is increased to make The pressure in the furnace rises to 6MPa. When the pressure in the furnace reaches 6MPa, the temperature is raised to 1460℃ at a heating rate of 20℃ / min and kept at this temperature for 10 minutes to perform instantaneous high-temperature activated liquid phase pressure sintering. Then, the pressure in the furnace is maintained at 6MPa, and the temperature in the furnace is lowered to 1430℃ at a cooling rate of 15℃ / min and kept at this temperature for 80 minutes to perform cooling liquid phase pressure sintering. After the insulation is completed, the furnace temperature is lowered to 1150℃ within 8 minutes, and then cooled to the discharge temperature.

[0048] F. Low temperature tempering: The ground and polished machined alloy is tempered in a tube furnace in high purity argon at 400°C for 6 hours.

[0049] According to the relevant standards described in Example 1, the results show that the porosity of the alloy is <A02, B00, and there is no decarburized phase and carburized phase. The microstructure of the alloy after corrosion by standard metallographic reagents was observed under a scanning electron microscope. The results show that the alloy has a two-phase homogeneous structure of WC hard phase and Ni-based solid solution bonding phase, no obvious abnormal growth of WC grains, the edges and corners of WC grains are in a passivated state, and the average grain size of WC in the alloy is 0.28μm. Transmission electron microscopy observation and analysis results show that there is a uniformly distributed Ni3Al nano-dispersed phase in the alloy bonding phase.

[0050] Example 3

[0051] A. Batching and dry premixing: WC powder with a specific surface area average particle size of 0.24 μm, carbonyl Ni powder with a Fisher particle size of 1.4 μm, and Cr3C2 powder with a Fisher particle size of 0.9 μm, VC powder with a Fisher particle size of 1.1 μm, Mo2C powder with a Fisher particle size of 0.8 μm, and AlN powder with a Fisher particle size of 0.7 μm, respectively, are batched so that the mass fraction of Ni in the raw material powder is 11.0%, the mass ratio of Cr3C2 to Ni is 9.0%, the mass ratio of VC to Ni is 4.0%, the mass ratio of Mo2C to Ni is 7.5%, and the mass ratio of AlN to Ni is 6.0%; the prepared raw material powders are then charged into a three-dimensional mixing device and dry mixed for 1.5 hours under a high-purity nitrogen protective atmosphere to prepare a premix;

[0052] B. Wet grinding: using a drum ball mill and WC-8Ni-based cemented carbide grinding balls with an average grain size of 0.7 μm, the mass ratio of grinding balls to premix is ​​4:1, the grinding balls, the premix obtained in step A, a polyethylene glycol forming agent accounting for 2.0% of the total mass of the mixture, and a mixed wet grinding medium of alcohol and hexane are added into the ball mill barrel, and the wet grinding time is 55 hours; the volume proportion of hexane in the wet grinding medium mixed solution is 8%, and the wet grinding medium liquid level is 7 cm higher than the solid phase reference plane of the balls and the material;

[0053] C. Drying and granulation: The wet-milled mixture is prepared into a spherical mixture with an average particle size of less than 150 μm by vacuum drying and mechanical granulation process;

[0054] D. Molding: According to the shape and size of the product, the spherical mixture is pressed into shape by compression molding and then cold isostatic pressing;

[0055] E. Forming agent removal and sintering: Forming agent removal and sintering are carried out in a 6MPa pressure sintering furnace. Forming agent removal is carried out in a hydrogen atmosphere according to the conventional polyethylene glycol removal process. Vacuum sintering is carried out at a heating rate of 3°C / min. When the temperature in the furnace rises to 1300°C, high-purity argon is introduced to make the pressure in the sintering furnace reach 8kPa and keep warm for 70 minutes. When the temperature in the furnace is raised to 1420°C at a heating rate of 5°C / min, the amount of high-purity argon in the furnace is increased to make the furnace The internal pressure rises to 4MPa. When the pressure in the furnace reaches 4MPa, the temperature is raised to 1450℃ at a rate of 10℃ / min and kept at this temperature for 15 minutes to perform instantaneous high-temperature activated liquid phase pressure sintering. Then, the pressure in the furnace is maintained at 4MPa, and the temperature in the furnace is lowered to 1420℃ at a rate of 20℃ / min and kept at this temperature for 60 minutes to perform cooling liquid phase pressure sintering. After the insulation is completed, the furnace temperature is lowered to 1100℃ within 5 minutes, and then cooled to the discharge temperature.

[0056] F. Low temperature tempering: The sintered alloy is tempered at 350°C in a tubular furnace in high purity nitrogen for 10 hours.

[0057] According to the relevant standards described in Example 1, the results show that the porosity of the alloy is <A02, B00, and there is no decarburized phase and carburized phase. The microstructure of the alloy after corrosion by standard metallographic reagents was observed under a scanning electron microscope. The results show that the alloy has a two-phase homogeneous structure of WC hard phase and Ni-based solid solution bonding phase, no obvious abnormal growth of WC grains, the edges and corners of WC grains are in a passivated state, and the average grain size of WC in the alloy is 0.30μm. Transmission electron microscopy observation and analysis results show that there is a uniformly distributed Ni3Al nano-dispersed phase in the alloy bonding phase.

[0058] Comparative Example 1

[0059] Except that rapid cooling is not used during sintering and tempering is not used after sintering, the alloy composition and preparation process are the same as those in Example 1. Figure 2 As shown in the figure, the microstructure of the alloy after being corroded by standard metallographic reagents was observed under a scanning electron microscope, and it was found that the edges and corners of the WC grains in the alloy were obviously sharpened.

[0060] Comparative Example 2

[0061] Except that two-stage liquid phase sintering is not used during sintering and tempering process is not used after sintering, the alloy composition and other preparation processes are the same as those in Example 1. The liquid phase sintering temperature is 1470°C. After 120 minutes of heat preservation, the furnace temperature is reduced to 1200°C within 12 minutes, and then cooled to the product outlet temperature by conventional furnace cooling. Figure 3 As shown in the figure, the microstructure of the alloy after being corroded by standard metallographic reagents was observed under a scanning electron microscope, and it was found that the WC grains in the alloy had obvious grain growth. Because the alloy is no longer in the category of ultrafine grains, the performance of the alloy was not tested.

[0062] Comparative Example 3

[0063] The alloy composition and other preparation processes are the same as those in Example 1, except that the raw material powder is not pre-mixed in a three-dimensional dry manner, but is directly loaded into the drum of a ball mill, polyethylene glycol molding agent and a single alcohol wet grinding medium are used, and vacuum drying and mechanical granulation are used. Figure 4 As shown in the figure, the microstructure of the alloy without metallographic corrosion was observed under a scanning electron microscope, and it was found that there was an obvious bonding phase (dark) aggregation area in the alloy. Due to the obvious microstructural defects in the alloy, the alloy properties were not tested.

[0064] Comparative Example 4

[0065] No Mo2C was added to the alloy. Vacuum drying and mechanical granulation were adopted. The other components in the alloy except WC and other preparation processes were the same as those in Example 2.

[0066] Comparative Example 5

[0067] Except that the tempering process is not used after sintering, the alloy composition and preparation process are the same as those in Example 3.

[0068] Comparative Example 6

[0069] No AlN bonding phase strengthening additive was added to the alloy, and no tempering process was used after sintering. The other alloy components except WC and the preparation process were the same as those in Example 3.

[0070] Comparative Example 7

[0071] The alloy composition and the preparation process before alloy sintering are the same as those in Example 3. Sintering is carried out in a conventional vacuum sintering furnace. No pressure is applied in the sintering furnace during the instantaneous high-temperature activated liquid phase sintering and cooling liquid phase sintering stages. After sintering and heat preservation, the alloy is cooled to the product discharge temperature by conventional furnace cooling, and no post-sintering tempering treatment is performed. According to the relevant standards described in Example 1, the results show that the alloy porosity is A08 and B08, and there are a large number of pores and holes in the alloy. Because the alloy porosity is seriously exceeded, the performance of the alloy is not tested.

[0072] The alloys prepared in the above embodiments and the alloys prepared in other comparative examples except those prepared in comparative examples 2, 3 and 7 with microstructure defects and coarse grains were measured for physical and mechanical properties using GB / T 3851-2015 "Method for Determination of Transverse Fracture Strength of Cemented Carbide" (selecting Type B specimen) and GB / T 7997-2014 "Method for Determination of Vickers Hardness of Cemented Carbide" (selecting 30kg load); the uniform corrosion rate of the samples treated with grinding-polishing-ultrasonic cleaning-drying was measured in 3.5% NaCl solution with reference to GB / T 39534-2020 "Method for Determination of Uniform Corrosion Rate of Stainless Steel and Nickel-Based Alloys in Corrosive Liquids of Metals and Alloys", and the test conditions were: continuous immersion at room temperature in a closed glass container for 30 days. The test results are shown in Table 1.

[0073] Table 1 Physical and mechanical properties of alloys in Examples and Comparative Examples and uniform corrosion rate test results in 3.5% NaCl solution

[0074]

Claims

1. A method for preparing high-strength, corrosion-resistant ultrafine-grained WC-Ni-based cemented carbide, characterized in that: include A. Batching and dry premixing: WC powder with a specific surface area average particle size of less than 0.25 μm, carbonyl Ni powder with a Fisher particle size of less than 1.5 μm, and Cr3C2 powder, VC powder, Mo2C powder and AlN powder with a Fisher particle size of less than 1.2 μm are batched so that the mass fraction of Ni in the raw material powder is 6.0-11.0%, the mass ratio of Cr3C2 to Ni is 8.0-10.0%, the mass ratio of VC to Ni is 3.0-4.0%, the mass ratio of Mo2C to Ni is 5.0-7.5%, and the mass ratio of AlN to Ni is 4.0-6.0%; then the prepared raw material powders are dry mixed for 1-1.5 hours under a protective atmosphere to prepare a premix; B. Wet grinding: wet grinding the cemented carbide grinding balls, premix, molding agent and wet grinding medium for 50 to 60 hours, wherein the mass ratio of cemented carbide grinding balls to premix is ​​4 to 5, and the molding agent is added in an amount of 2.0 to 2.3% of the total mass fraction of the powder; C. Drying and granulation: using spray drying granulation or vacuum drying and mechanical granulation process to prepare the wet-milled mixture into a spherical mixture with an average particle size of less than 150 μm; D. Molding: According to the shape and size of the product, the spherical mixture is pressed into shape; E. Removal of forming agent and sintering: a. Remove the forming agent from the green compact; b. Raise the temperature at a heating rate of 3 to 5°C / min for vacuum sintering. When the sintering furnace temperature rises to 1300 to 1350°C, introduce high-purity argon gas to make the pressure in the furnace reach 6 to 8 kPa, and keep it warm for 50 to 70 minutes; c. Raise the temperature in the furnace to 1420 to 1440°C at a heating rate of 5 to 10°C / min, and then increase the amount of high-purity argon gas in the furnace to raise the pressure in the sintering furnace to 4 to 8MPa; d. Maintain the pressure in the furnace at 4-8MPa, continue to heat up to 1450-1470℃ at a rate of 10-20℃ / min, and keep warm for 10-15 minutes; e. Continue to maintain the pressure in the furnace at 4-8MPa, cool down to 1420-1440℃ at a rate of 10-20℃ / min, and keep warm for 60-100 minutes; f. Reduce the furnace temperature to 1100-1200℃ within 5-10 minutes; g. Cool with the furnace to the product discharge temperature; F. Low temperature tempering: The tempering temperature is 350-450℃, the tempering time is 3-10 hours, and it is carried out under a protective atmosphere.

2. The method for preparing a high-strength, corrosion-resistant ultrafine-grained WC-Ni based cemented carbide according to claim 1, characterized in that: The dry mixing of raw material powders into a premix in step A is carried out in a three-dimensional motion dry mixing device.

3. The method for preparing a high-strength, corrosion-resistant ultrafine-grained WC-Ni based cemented carbide according to claim 1, characterized in that: The protective atmosphere in step A is high-purity argon or high-purity nitrogen.

4. The method for preparing a high-strength, corrosion-resistant ultrafine-grained WC-Ni based cemented carbide according to claim 1, characterized in that: The wet grinding in step B is carried out in a drum ball mill.

5. The method for preparing a high-strength, corrosion-resistant ultrafine-grained WC-Ni based cemented carbide according to claim 1, characterized in that: The grinding ball material in step B is WC-Ni based cemented carbide with an average grain size of WC hard phase less than 0.8 μm.

6. The method for preparing a high-strength, corrosion-resistant ultrafine-grained WC-Ni based cemented carbide according to claim 1, characterized in that: The wet grinding medium in step B is a mixed solution of alcohol and hexane, the volume proportion of hexane in the wet grinding medium mixed solution is 5-10%, and the wet grinding medium liquid level is 5-7 cm higher than the ball and material solid phase reference level.

7. The method for preparing a high-strength, corrosion-resistant ultrafine-grained WC-Ni based cemented carbide according to claim 1, characterized in that: In step B, the molding agent is polyethylene glycol or paraffin.

8. The method for preparing a high-strength, corrosion-resistant ultrafine-grained WC-Ni based cemented carbide according to claim 1, characterized in that: The protective atmosphere in step F is vacuum or high-purity argon or high-purity nitrogen inert gas.

9. The method for preparing a high-strength, corrosion-resistant ultrafine-grained WC-Ni based cemented carbide according to claim 1, characterized in that: Before step F of low temperature tempering, the sintered product may be subjected to mechanical processing.

Citation Information

Patent Citations

  • High-hardness high-strength low-cost nonmagnetic hard alloy

    CN101205584A

  • Tungsten-nickel-based enhanced hard alloy and preparation method thereof

    CN107964620A

  • Superfine particle hard alloy as well as preparation method and application thereof

    CN116121615A

  • WC grain hard alloy capable of generating Ni3Al in situ and preparation method of WC grain hard alloy

    CN117965990A